AN EFFICIENT ARTIFICIAL BEE COLONY ALGORITHM FOR A P-HUB COVERING LOCATION PROBLEM WITH TRAVEL TIME RELIABILITY - Sadeghi, Marjan; Tavakkoli Moghaddam, Reza; Babazadeh, Reza (International Journal of Industrial Engineering: Theory, Applications and Practice, 2018)
This paper addresses a new reliable p-hub covering location problem (p-HLP) in a degradable transportation network. The capacity of links is assumed as uniform random variables subject to stochastic degradations, as in a form of daily traffic, earthquake, flood, etc. Stochastic degradations cause some uncertainties in a network, such as travel time uncertainty. As a result, this paper tackles with uncertainty in a degradable network by the stochastic programming and travel time budget concept. An artificial bee colony (ABC) algorithm is proposed to solve real-sized instances, and its performances are compared with a differential evolution (DE) algorithm. Finally, some computational experiments are provided to demonstrate the effectiveness of the proposed model and solution approaches.